Studies on Polypropylene Gill Nets - K.V., Mohan Rajan; P., George Mathai; R.S., Manoharadoss; Puthra, Pravin (Fishery Technology, 2025)
Comparative studies on the fishing efficiency of Nylon and Polypropylene gill nets were carried out to ascertain the suitability of Polypropylene twine for fabrication ofgill nets. It was found that Polypropylene was as goodas Nylon in terms ofoverall catch landed and more efficient for the quality fish seer. The Polypropylene proved to be a cost effective altcmative to Nylon for gill nets.